Identifikasi Niat dan Keputusan Pembelian berdasarkan Electronic Word of Mouth (e-WOM), Penggunaan Media Sosial, Logo dan Reputasi Perusahaan - Nurhayani, Endah; Abadi, Feryal (SAFE-Network, 2024)
This study aims to identify purchase intention and decision based on electronic word of mouth (e-WOM), social media usage, logo and company reputation with trust as an intervening by understanding consumer purchasing behavior in the flat glass industry. This study is supported by using a purposive sampling method involving 180 flat glass consumers. Some findings in this study are e-WOM, social media usage, and logo do not have a positive direct effect on purchase intention. E-WOM and logo have a positive effect on purchase intention mediated by trust. Social media usage does not have a positive effect on purchase intention mediated by trust. Then, e-WOM, social media usage, and logo do not have a positive effect on purchase decision mediated by trust. There is a positive effect on purchase intention and purchase decision. Company reputation can strengthen the positive relationship between e-WOM and social media usage with purchase intention. The managerial implications of this study for organizations are to strengthen marketing intelligence because it can optimize company performance and commit to continuing to conduct satisfaction surveys to measure the level of consumer satisfaction so that consumer purchase decision continues to increase.